Applications of 3D printing in TKR Pre surgical planning for Design Optimization – A Case Study. (2018) - Sandeep Kumar, Y.; Rao KVS, Rajeswara; Yalamalle, Sunil R; Venugopal, SM; Krishna, Sandeep
Abstract: In traditional preoperative planning orthopedic surgeons utilized 2D plain X-Ray images are used to access the bone anatomy of patients, which results more surgical time, heavy intraoperative blood loss and more tissue removal under the tibia and femoral cut. Consequently the surgeon can perform satisfactory reconstruction of knee joint using the images produced through Computer Tomography (CT) and Magnetic Resonance Imaging (MRI) image processing techniques with minimal of said losses. The 3D model of patient knee is produced by interfacing the CT scan data with 3D slicer software. 3D printer can produce solid 3D physical objects using STL file, this can be used in surgical planning to overcome many limitations of 2D imaging.